RNF130 Regulates LDLR Availability and Plasma LDL Cholesterol Levels. Issue 7 (6th March 2023) - Clifford, Bethan L.; Jarrett, Kelsey E.; Cheng, Joan; Cheng, Angela; Seldin, Marcus; Morand, Pauline; Lee, Richard; Chen, Mary; Baldan, Angel; de Aguiar Vallim, Thomas Q.; Tarling, Elizabeth J.
Abstract : Background: Removal of circulating plasma low-density lipoprotein cholesterol (LDL-C) by the liver relies on efficient endocytosis and intracellular vesicle trafficking. Increasing the availability of hepatic LDL receptors (LDLRs) remains a major clinical target for reducing LDL-C levels. Here, we describe a novel role for RNF130 (ring finger containing protein 130) in regulating plasma membrane availability of LDLR. Methods: We performed a combination of gain-of-function and loss-of-function experiments to determine the effect of RNF130 on LDL-C and LDLR recycling. We overexpressed RNF130 and a nonfunctional mutant RNF130 in vivo and measured plasma LDL-C and hepatic LDLR protein levels. We performed in vitro ubiquitination assays and immunohistochemical staining to measure levels and cellular distribution of LDLR. We supplement these experiments with 3 separate in vivo models of RNF130 loss-of-function where we disrupted Rnf130 using either ASO (antisense oligonucleotides), germline deletion, or AAV CRISPR (adeno-associated virus clustered regularly interspaced short palindromic repeats) and measured hepatic LDLR and plasma LDL-C. Results: We demonstrate that RNF130 is an E3 ubiquitin ligase that ubiquitinates LDLR resulting in redistribution of the receptor away from the plasma membrane. Overexpression of RNF130 decreases hepatic LDLR and increases plasma LDL-C levels. Further, in vitro ubiquitination assays demonstrate RNF130–dependent regulation of LDLR abundance at the plasma membrane. Finally, in vivo disruption of Rnf130 using ASO, germline deletion, or AAV CRISPR results in increased hepatic LDLR abundance and availability and decreased plasma LDL-C levels. Conclusions: Our studies identify RNF130 as a novel posttranslational regulator of LDL-C levels via modulation of LDLR availability, thus providing important insight into the complex regulation of hepatic LDLR protein levels.